Pengembangan Buku Guru Matematika SD Berbasis Kognisi - Widayati, Widayati; Mujidin, Mujidin (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
The books available can be said to be good, but there are still many teachers who have difficulty conveying the material to elementary school students. Many teachers also do not pay attention to children's cognitive development, so that mathematics learning is less enjoyable and students are less motivated. With the development of this Mathematics Teacher's Guidebook, it makes it easier for teachers to explain concepts from mathematics material. The aim of this research is to create a Grade 3 Mathematics Teacher's Guidebook, as well as determine the feasibility of the Mathematics Teacher's Guidebook. This research uses descriptive qualitative and quantitative methods. The instruments used in this research are the results of observations, teaching reflections, tests, questionnaires, Learning Implementation Plans (RPP). Qualitative data analysis techniques by reducing data refer to selecting, focusing, simplifying, abstracting and transforming "raw data" that occurs in written field notes. For quantitative data analysis, the population of grade 3 SD Muhammadiyah Warungboto Yogyakarta. Data collection techniques use tests. The quantitative data analysis technique uses the Wilcoxon Test. The assessment carried out by lecturers and teachers on the book is in the very good category, meaning it is suitable for use in elementary mathematics learning. Teachers are easy to convey the material so that elementary school students no longer experience difficulties in understanding concepts in Mathematics lessons. Keywords: Books, Mathematics, cognition